2002
DOI: 10.1152/ajpregu.00393.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin-18 on mouse core body temperature

Abstract: We have studied, using a telemetry system, the pyrogenic properties of recombinant murine interleukin-18 (rmIL-18) injected into the peritoneum of C57BL/6 mice. The effect of IL-18 was compared with the febrile response induced by human IL-1beta, lipopolysaccharide (LPS), and recombinant murine interferon-gamma (rmIFN-gamma). Both IL-1beta and LPS induced a febrile response within the first hour after the intraperitoneal injection, whereas rmIL-18 (10-200 microg/kg) and rmIFN-gamma (10-150 microg/kg) did not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…Such a possibility is not without precedence. For example, another study has found that IL-18 negated the febrile effect associated with IL-1␤ (Gatti et al, 2002). In summary, the role of IL-18 in exacerbating neuroinflammation along with its inhibitory role in remyelination indicate that inhibition of IL-18 may prove to be a valuable therapeutic approach for demyelinating diseases such as MS.…”
Section: Il-18mentioning
confidence: 96%
“…Such a possibility is not without precedence. For example, another study has found that IL-18 negated the febrile effect associated with IL-1␤ (Gatti et al, 2002). In summary, the role of IL-18 in exacerbating neuroinflammation along with its inhibitory role in remyelination indicate that inhibition of IL-18 may prove to be a valuable therapeutic approach for demyelinating diseases such as MS.…”
Section: Il-18mentioning
confidence: 96%
“…Discussion IL-1␤, IL-18, COX-2, and Fever. The present study was performed to examine the differences between IL-1␤ and IL-18 for the induction of COX-2, because injection of IL-18 does not cause fever in animals (5,17,18). These data are in sharp contrast to the ability of IL-1 to produce fever in animals and humans at exceedingly low doses of a few nanograms per kilogram (13).…”
Section: Cox-2 Protein and Pge2 Levels After Il-18mentioning
confidence: 97%
“…Although IL-18 has been reported to induce COX-2 gene expression in the articular chondrocytes (16), IL-18 does not cause fever (5,17,18), which depends on COX-2 (3,4). Humans, who are highly responsive to the rapid pyrogenic response of i.v.…”
mentioning
confidence: 99%
“…Although they share certain proinflammatory activities, they also have very important individual functions. For example, IL-1␤ but not IL-18 is anorectic (40,41), pyrogenic (42,43), results in skin rashes and urticaria, induces hepatic-acute phase proteins (44,45), up-regulates prostanoid synthesis, and is involved in inflammatory pain hypersensitivity (46). IL-1␤ is also implicated in destructive joint and bone disease (47), tumor angiogenesis and invasiveness (48), and toxicity of insulin-producing pancreatic islets ␤ cells (49), and neurons in stroke and neurodegeneration (50).…”
Section: Biological Activities Of the Prime Caspase-1 Substrates Il-1mentioning
confidence: 99%